Mengembangkan Kualitas Usaha Desa Wisata: Perancangan Sistem Usaha pokdarwis dengan Menggunakan Model Kemitraan - arifin, samsul (Universitas Islam Nahdlatul Ulama Jepara, 2022)
Villages can manage resources independently, one of which is through Village-Owned Enterprises (BUMDes), this is a form of empowerment from the government in the form of autonomy. This research was conducted in Tanjung Village, Jepara Regency. The approach used in this research is Tetrapreneur and resource-based view theory. Tetrapreneur is divided into several models, namely; Chainpreneur, Marketpreneur, Qualitypreneur, Brandpreneur. The second approach is the resource-based view theory. This theory is used as the basis for selecting a tourism village business unit that must have a competitive advantage and distinctive features to contribute to improving the welfare of the people of Tanjung Village. With activities like this, it can help pokdarwis to map the conditions of village entrepreneurship (Chainpreneur), Quality (Qualitypreneur), Market (Marketpreneur), and Brand (Brandpreneur). Therefore, developing the quality of village-owned businesses (Q-BUMDes) is recommended to form an integrated database system to control tourism village entrepreneurs. Q-BUMDes that can be done include mapping of facilitators, mentors, and assistance funds that are updated regularly. The application of the Tetrapreneur model in Tanjung Village is expected to become a role model for other villages, especially in Jepara Regency as a model of sustainability in poverty alleviation without leaving local wisdom.